TWISTED OVARIAN CYSTS IN PREGNANCY: BALANCING CONSERVATIVE AND SURGICAL MANAGEMENT FOR OPTIMAL OUTCOMES - Rumapea, Costan Tryono Parulian; Saputra, Dikki; Sonya, Marta; Irvan, Muhammad (Jurnal Keperawatan dan Kesehatan, 2025)
Objective: Ovarian cysts are commonly detected in pregnancy due to routine prenatal ultrasonography. Most are benign and resolve spontaneously, but some may cause complications, risking both mother and fetus. Case Report: A 23-year-old primigravida at 30-31 weeks of gestation presented for routine antenatal care. She had a history of laparotomy and left salpingo-oophorectomy at 11 weeks 3 days pregnant due to ovarian torsion. A 9.16 × 6.32 cm left ovarian cyst with a depth of 5.13 cm was detected early in pregnancy and managed conservatively. However, due to worsening pain, surgical intervention was performed. At the current visit, she was asymptomatic, and ultrasound confirmed a viable singleton pregnancy with normal fetal parameters. Vaginal delivery was recommended. Conclusion: This case highlights the importance of timely diagnosis and appropriate management of ovarian cysts in pregnancy. A balance between conservative monitoring and surgical intervention is crucial to ensure optimal maternal and fetal outcomes.